14.5k views
0 votes
Use the given functions to find f (g(x)), and give the restrictions on x.

F(x)= 1/x-3 and g(x) = 3/x +3

F(g(x)) = ?

Where x(doesn’t = ?

1 Answer

5 votes

Answer:


f(g(x)) = (10x-9)/(3 + 3x)

Explanation:

Given


f(x) = (1)/(x) - 3


g(x) = (3)/(x) + 3

Required

Find f(g(x))

If:
f(x) = (1)/(x) - 3

Then:


f(g(x)) = (1)/(3/x + 3) -3

Solve the denominator (take LCM)


f(g(x)) = (1)/((3+3x)/(x)) -3


f(g(x)) = (x)/(3 + 3x) - 3

It can be solved further as:


f(g(x)) = (x-3(3 + 3x))/(3 + 3x)


f(g(x)) = (x-9 + 9x)/(3 + 3x)


f(g(x)) = (10x-9)/(3 + 3x)

User Mudasir Sharif
by
6.5k points